Infusion of Non-HLA-Matched Off-the-Shelf Ex Vivo Expanded Cord Blood Progenitors in Patients Undergoing Cord Blood Transplantation: Result of a Phase II Clinical Trial - Milano, F.; Thur, L.A.; Blake, J.; Delaney, C. (Frontiers in Cell and Developmental Biology, 2022)
Myeloablative cord blood transplant (CBT) recipients experience delayed hematopoietic recovery and an increased risk of transplant related mortality (TRM). We developed methods for ex vivo expansion and cryopreservation of CB stem and progenitor cells. Between September 2010 and August 2012, 15 patients with hematologic malignancies were enrolled in this single center Phase II trial to assess the safety of infusing a non-HLA-matched expanded CB product to augment conventional CBT. On the day of transplant, the primary graft (1 or 2 unmanipulated CB units) was infused first followed 4 hours later by infusion of the expanded CB product. All patients engrafted. Median time to neutrophil and platelet recovery was 19 and 35 days, respectively. Early myelomonocytic recovery was almost entirely due to cells arising from the non-HLA-matched expansion product and were no longer detected at day 14 in all but 2 patients. The probability of 3-year disease free survival was 86%. No TRM was observed throughout the study period, and only 2 patients relapsed. All patients presented with grade II acute graft-versus-host disease (aGVHD) at a median time of 32 days, with no grade III-IV aGVHD observed. At 2 years only 2 patients remain on immunosuppressive therapy for mild chronic GVHD. The results of this Phase II safety study demonstrate that infusion of an off-the-shelf non-HLA-matched expanded CB product to augment a CB graft was safe and led to sustained myeloid recovery. Based on these very promising results, a prospective multicenter randomized trial utilizing this product has been conducted and results will be soon released. ClinicalTrials.gov Identifier: NCT01175785